Leadership as a basis for excellence in the organizational climate - Garcia Manga, Marta; Llovet, Rafa; Pastor Tejedor, Ana Clara (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Today, companies seek global excellence of his performance from excellence in different aspects of the organization. To achieve optimal levels of quality can apply some self evaluating Models of Excellence as to improve different aspects of the organization. One of these is the EFQM Excellence Model (European Foundation for Quality Management). One of the most important areas in a company is its human resources and, therefore, the Organizational climate. In the EFQM Excellence Model there are two sections about this subject (People and Leadership). This paper analyzes the different factors influencing the organizational climate of a company. The factors discussed are the cause of business excellence, according to the EFQM model. A major influence is the Leadership. You could say that Leadership is the foundation of a good organizational climate. Thus, one can show how a company that takes a strategic decision to improve the organizational climate, needs a leader able to convey these decisions to staff and make that they feel them yours. Furthermore, this study will apply in a case study using a questionnaire about organizational climate. Thus, we can test hypotheses by analyzing the results. Literature Review And Hypotheses According to Bass (1985) there are two types of leadership. A "low level" based on the exchange of rewards between leaders and followers (pay, promotions ...) called transactional leadership. This type of leadership adequately implemented has positive effects on subordinates and the organization, but this leadership is limited. The other is the transformational leadership that is capable of changing the values and beliefs, and attitudes of people working with him, increasing the effectiveness of their work unit beyond what is expected. This type of leadership, there may be greater or lesser degree, in any organization and any level of it. Are these leaders that, under appropriate circumstances, create and transform organizational cultures. And, specifically, the section on organizational climate. Transformational leadership encourages peers or colleagues and followers to consider their work from different perspetives, make them aware of the mission or vision of the organization, to facilitate the maximum development potential and motivate them to further their own interests, taking into account group interests and the overall organization. The transformational leader would be an extension of the concept of charismatic leadership. Although charisma is a necessary condition for transformational leadership but not sufficient, the charismatic influence over his followers and transformational get an identification of supporters or equal to their leader. Masi and Cooke (2000) conducted a study that found that there is a significant positive relationship between transformational leadership, staff motivation and the degree of commitment to the quality of organizational performances. Building on this, we propose that leadership is a key fator in the organizational climate. And further, one might say that leadership is a basis for excellence in the organizational climate. And that potential changes in the organizational climate must go through a leader who can make employees assimilate these changes, and even make them themselves.